The spatial and temporal effect of electrochromic windows on indoor and human microbiome in an inpatient hospital - Man In Lam; Kelsey Gleason; Allen B. Repp; Sam Yeo; Kinga Vojnits; Piers MacNaughton; Sepideh Pakpour (Antimicrobial Stewardship & Healthcare Epidemiology)
Abstract